Comparative & international library science, editado por John F. Harvey - Miranda, Antonio (Revista de Biblioteconomia de Brasília, 1978)
HARVEY, John F. (ed.). Comparative & international library science. Metuchen, N. J.: Scarecrow Press, 1977. 286 p. ISBN 0 8108 1060 3.